Structure, stability and permeation properties of NaA zeolite membranes for H2O/H2 and CH3OH/H2 separations. Issue 1 (January 2018) - Lee, Sang Moon; Xu, Nong; Grace, John R.; Li, Anwu; Lim, C. Jim; Kim, Sung Su; Fotovat, Farzam; Schaadt, Achim; White, Robin J.
Abstract: NaA zeolite membranes were synthesised in the secondary growth hydrothermal method based on the seeding of the inner surface of a ceramic α-alumina tube. The impacts of crystallisation time and zeolite precursor concentration (in H2 O) were investigated. The structure and stability of the prepared NaA zeolite membranes were also investigated with operating temperatures, times and pressures. The results indicate that the optimal synthesis gel molar composition was 3Na2 O: 2SiO2 : Al2 O3 : 200H2 O. This led to cubic-shaped NaA zeolite which showed good stability. The optimal NaA zeolite membrane had H2 O and CH3 OH fluxes of 2.77 and 0.19 kg/m 2 h, with H2 O/H2 and CH3 OH/H2 separation factors of ∞ and 0.09 at a temperature of 30 °C. The NaA zeolite membrane had high thermal stability, but poor separation performance at high temperature (240 °C). The results suggested that the H2 permeation flux is significantly influenced by preferential adsorption of vapour in the NaA zeolite membrane.